Examining Futuwwa Organizations Using Process Tracing - Onur Dündar (Sosyal Siyaset Konferansları Dergisi)
This paper examines futuwwa [young manliness/chivalry] organizations in the following four different styles: (1)pre-Islamic futuwwa, (2)Abbasid futuwwa, (3)Sufi futuwwa, and (4)Akhi futuwwa organizations. The study investigates the dominance futuwwa organizations had over the economy with regard to these four different styles and attempts to question whether a relationship existed with the dominance of the central state authority during the periods when these types of futuwwa organizations were dominant. As a result of this investigation, the paper then attempts to test the conceptual framework used herein, which has three main components: the structuralist, institutionalist, and social network models. The presence of a significant relationship between the effectiveness of futuwwa organizations and the dominance of the central state authority will allow testing of the structuralist model. The paper tests the institutional and social network models by answering the questions of how and under what conditions this relationship had occurred. The article uses qualitative research methods for testing the conceptual framework and prefers the case study design, a qualitative research design. The study identifies cross-sectional cases and sub-cases in this context and resolves the data collected in the document analysis using the process tracing method.